ANALISIS PENGETAHUAN KONSEP (K3) LABORATORIUM KIMIA DI MAN 2 KOTA SEMARANG - Fela Citra Pertiwi; Eko Yuliyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Occupational Health and Safety known as Kesehatan dan Keselamatan Kerja (K3) is one of actions to provide safe and healthy workplace which is free from enviromental poluution, so that is could reduce the risk of work accident, and it improves the work producticity. The aim of this research is to know how far the implementaion of Occupational Health and Safety in MAN 2 Kota Semarang. The researcher used observation and interview method, which involved some of science student. The researcher also distributed questionnaire and interviewed chemistry teacher. The researcher took 126 student from four classes as researchobject. Based on the data obtained are as follows: knowledge on the hazard and safety in the laboratory of 65.80%, understanding of laboratory tools by 56%, the ability of the use of laboratory glassware by 44%, the ability of the use of non-glass laboratory equipment 34.10 % and material knowledge of 45%. Based on the results of research and analysis conducted, it can be concluded that the application (K3) chemistry laboratory in MAN 2 Kota Semarang is quite low, so that the impact of understanding and knowledge of students about (K3) in the laboratory is also low.  Keywords : Occupational Health and Safety, Student, MAN 2 Kota Semarang